Attitude towards the use of Information and Communication Technologies for teaching university professors in the context of COVID-19 (Revista Innova Educación, 2021)
The objective of the research was to determine the attitude towards the use of Information and Communication Technologies for the teaching (ICT) in teachers of the José Faustino Sánchez Carrión National University of Huacho in times of COVID-19. The research design was non-experimental, descriptive, cross-sectional, and quantitative. The sample was compound for 65 teachers of both genders from the Faculty of Business Sciences between designated and hired, and it was non-probabilistic. The instrument used for data collection was a questionnaire of the liker scale type centered on 3 sections. As a result, it was found that most teachers have favorable attitudes towards the use of ICT and statically significant differences were found between attitude towards ICT and the age group of teachers.
Keywords: TICE; teaching; university; COVID-19